An Improved Method for the Complete Hydrogenation of Aromatic Compounds under 1 Bar H2 with Platinum Nanowires. Issue 10 (24th July 2013) - Yu, Tingting; Wang, Jiaqing; Li, Xinming; Cao, Xueqin; Gu, Hongwei
<x xml:space="preserve">Abstract</x> A little pressure for a lot of gain: An efficient method has been developed for the controlled hydrogenation of phenol using a platinum nanowire catalyst under mild conditions (>98.4 %, 1 atm H2, 60 °C). The catalyst also exhibited high levels of activity and selectivity towards other selected aromatic compounds bearing a variety of different substituents, demonstrating its generality towards the hydrogenation of aromatic compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>